2014
DOI: 10.1177/1553350614552731
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Related Risk Factors for Recurrence After Inguinal Hernia Repair

Abstract: We found that female sex, direct inguinal hernias at the primary procedure, operation for a recurrent inguinal hernia, and smoking were significant risk factors for recurrence after inguinal hernia surgery. This knowledge of patient-related risk factors for recurrence after inguinal hernia surgery could be implemented in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
139
3
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(163 citation statements)
references
References 73 publications
8
139
3
13
Order By: Relevance
“…Inguinal hernia repair is the most frequent and resource-consuming surgical intervention in the UK. 1,2 It is also the most common general surgical intervention performed in Europe 1,3,4 and the USA. 5 Various surgical techniques and approaches are available for inguinal hernia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inguinal hernia repair is the most frequent and resource-consuming surgical intervention in the UK. 1,2 It is also the most common general surgical intervention performed in Europe 1,3,4 and the USA. 5 Various surgical techniques and approaches are available for inguinal hernia.…”
Section: Introductionmentioning
confidence: 99%
“…4 In the Netherlands, approximately 30,000 inguinal hernia repairs are carried out annually. In the USA, data from the National Centre for Health Statistics suggest that approximately 800,000 groin hernia repairs were performed in 2003, with over 90% of these surgeries performed on an outpatient basis.…”
Section: Introductionmentioning
confidence: 99%
“…Burcharth in a review of the Danish hernia registry reported an overall inguinal hernia reoperation rate of 3.8%. He acknowledged re-operation rates underestimate recurrence rates (18). Other studies have reported rates that do not widely differ from ours (19).…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that up to 13 % 4 of the procedures performed to treat a recurrence of an inguinal hernia, identifying among the risk factors for recurrence of inguinal hernia: anesthesia methods, techniques of mesh attachment, surgeon experience, gender patient, type of hernia, genetics, anatomical malformations of the abdominal wall, composition of connective tissue, smoking and postoperative care, impacting each in varying degrees for recurrence. 2,5 The National Health Information System in Mexico, reported from 2000 to 2007 approximately 282,105 cases of abdominal wall hernia repairs, being one of the most common procedures in the General Surgery and Pediatric Surgery Departments. 10 to 15% of the population is affected with this entity, having direct economic consequences in almost 25% of the economically active population.…”
Section: Introductionmentioning
confidence: 99%
“…2 Inguinal hernias are one of the most common reasons of primary care and possible surgical evaluation.…”
Section: Introductionmentioning
confidence: 99%